Pemanfaatan Limbah Sedotan Plastik sebagai Media Lekat dalam Proses Anammox: Utilization of Waste Plastic Straws as Carrier in the Anammox Process - Zulkarnaini; Annisa Aulia Rasyidah; Ridwan (BRIN Publishing (Penerbit BRIN), 2023)
Anaerobic ammonium oxidation (anammox) bacteria tend to settle in the reactor due to self-granulation capability. Carrier is used to enhancing nitrogen removal by anammox biofilm. This study analyzed nitrogen removal using plastic straws as carriers and compared nitrogen removal at different heights of the reactor. The study was conducted using an up-flow anaerobic sludge blanket (UASB) reactor with a volume of 300 mL with three sampling points of 8, 16, and 24 cm and operated for 72 days continuously. The artificial wastewater containing 70 mg-N/L ammonium and nitrite was continuously delivered into the reactor with a hydraulic retention time (HRT) of 6 hours and 3 hours. Cultivated anammox bacteria from Lake Koto Baru, Indonesia, was inoculated into the reactor to start the experiment. The nitrogen removal performance was calculated based on the influent and effluent concentrations of ammonium, nitrate, and nitrite. The nitrogen removal performance achieved a nitrogen removal rate (NRR) of 0.96 kg-N/m3·d, nitrogen removal efficiency (NRE) of 74.62%, and ammonium conversion efficiency (ACE) of 87%. This study shows that nitrogen removal can be optimized by using plastic straws as the carrier. The nitrogen removal mainly occurred in the bottom of the reactor where the average nitrogen removal at 1/3, 2/3, and top of reactor height was 60, 30, and 10%, respectively. Abstrak Bakteri anaerobic ammonium oxidation (anammox) cenderung mengendap di dasar reaktor karena kemampuannya untuk membentuk granular. Media lekat sering digunakan untuk meningkatkan penyisihan nitrogen berupa biofilm anammox. Penelitian ini bertujuan untuk menganalisis penyisihan nitrogen menggunakan sedotan plastik sebagai media lekat dan membandingkan penyisihan nitrogen pada ketinggian reaktor. Penelitian dilakukan menggunakan reaktor up-flow anaerobic sludge blanket (UASB) bervolume 300 mL dengan 3 titik sampling yaitu pada ketinggian 8, 16, dan 24 cm yang dioperasikan selama 72 hari. Bakteri anammox yang telah dikultivasi dari Telaga Koto Baru, Kabupaten Tanah Datar, Sumatra Barat, diinokulasikan ke dalam reaktor untuk memulai percobaan. Air limbah artifisial yang mengandung 70 mg-N/L amonium dan nitrit dialirkan ke dalam reaktor secara kontinu dengan hydraulic retention time (HRT) 6 jam dan 3 jam. Kinerja penyisihan nitrogen dihitung berdasarkan konsentrasi amonium, nitrit dan nitrat. Penyisihan nitrogen maksimal mencapai nitrogen removal rate (NRR) 0,96 kg-N/m3.h, nitrogen removal efficiency (NRE) 74,62%, dan ammonium conversion efficiency (ACE) 87%. Penelitian ini menunjukkan bahwa penyisihan nitrogen dapat dioptimalkan dengan menggunakan sedotan plastik sebagai media. Penyisihan nitrogen terutama terjadi di bagian bawah reaktor di mana rata-rata penyisihan nitrogen pada 1/3, 2/3, dan paling atas ketinggian reaktor masing-masing adalah 60, 30, dan 10%.